Contextualising the Socialisation of Muslim Minorities within Parental Upbringing Values in the Netherlands: The Case of Moroccan-Dutch - Chafai, Habiba (Journal of Muslims in Europe, 2021)
Abstract The objective of the present review article is to position the role of parents from Muslim backgrounds in shaping the participation and socialisation of their children in Dutch society. It particularly seeks to contextualise the topic among Moroccan-Dutch parents from a cultural perspective by discussing gender issues, religiosity, identity and parental upbringing. The review begins by providing a context on Moroccan-Dutch migration history, religious and cultural background, and socio-economic status. It aims to explore the relationship between the transmission of parental upbringing and the socialisation of children by discussing the representation of Muslims in the media, the portrayal of Muslim women in the integration discourse, markers of identity and sense of belonging, and the impact of parental upbringing values.